Examining the relationship between structural factors, individual characteristics, and homelessness - Wood, Gavin; Johnson, G.; Scutella, R.; Tseng, Y. (2015)
This report examines interactions between macro structures such as changes to housing and labour markets, and the micro processes that render individuals vulnerable to homelessness.